2022
DOI: 10.1002/jmv.28264
|View full text |Cite
|
Sign up to set email alerts
|

A phenome‐wide investigation of risk factors for severe COVID‐19

Abstract: With the continued spread of COVID‐19 globally, it is crucial to identify the potential risk or protective factors associated with COVID‐19. Here, we performed genetic correlation analysis and Mendelian randomization analysis to examine genetic relationships between COVID‐19 hospitalization and 405 health conditions and lifestyle factors in 456 422 participants from the UK Biobank. The genetic correlation analysis revealed 134 positive and 65 negative correlations, including those with intakes of a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 75 publications
3
20
0
2
Order By: Relevance
“…A meta-analysis concluded that asthma was not associated with higher SARS-CoV-2 infection or a worse prognosis and that patients with asthma had lower mortality than those without asthma 39 . Previous MR analysis studies have also suggested that asthma was a protective factor for SARS-CoV-2 infection and severe COVID-19 7,8 . Although similar results were obtained only in the multivariate MR analysis with AR and AD as references, the two-sample MR analysis of asthma-severe COVID-19 in this study was negative.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A meta-analysis concluded that asthma was not associated with higher SARS-CoV-2 infection or a worse prognosis and that patients with asthma had lower mortality than those without asthma 39 . Previous MR analysis studies have also suggested that asthma was a protective factor for SARS-CoV-2 infection and severe COVID-19 7,8 . Although similar results were obtained only in the multivariate MR analysis with AR and AD as references, the two-sample MR analysis of asthma-severe COVID-19 in this study was negative.…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, in contrast to traditional epidemiologic methods, the MR study can suggest the directionality of exposure and outcome, and thus a causal relationship rather than an association 6 . A relatively comprehensive MR study showed that physical activity, high education level, never smoking, and asthma were protective factors against hospitalized COVID-19 7 . It was also suggested through MR analysis that asthma was a protective factor for SARS-CoV-2 infection 8 .…”
Section: Introductionmentioning
confidence: 99%
“…(3) This article focuses on brain cell-types but it must be acknowledged that there are many other risk factors for Long Covid. E.g., in 456 422 participants from the UK Biobank, Baranova et al performed a Mendelian randomization analysis to examine relationships between COVID-19 hospitalization and health conditions, finding that a set of body fat-related traits, maternal smoking around birth, basal metabolic rate, lymphocyte count, peripheral enthesopathies and allied syndromes, blood clots in the legs, and arthropathy, are causal risk factors for severe COVID-19, while higher education attainment, physical activity, asthma, and never smoking status protect against the illness [87]. In order for these to affect mental functions, they must relate to brain cell-types, although the molecular connections are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…MR can diminish the issues of unmeasured confounding and reverse causation, because genetic variants are randomly assorted at conception and are not modified by the progression of disease (Smith and Ebrahim, 2003). Recently, the MR approach has been successfully applied to shed light on the causal roles of smoking and alcohol consumption in a wide range of health outcomes (Rao et al, 2021;Larsson and Burgess, 2022;van de Luitgaarden et al, 2022;Zhang and Baranova, 2022;Baranova et al, 2023). Herein, we applied the MR design to explore the potential causal associations of smoking as well as alcohol consumption with frailty.…”
Section: Reviewed Bymentioning
confidence: 99%